Prophylactic Moxibustion in Preventing Postoperative Urinary Retention of Hemorrhoidectomy: A Study Protocol for a Randomized Controlled Trial - Ji, Lijiang; Wang, Aihua; Fan, Qian; Zhang, Naijin; Weng, Liping; Gu, Jing (Frontiers in Surgery, 2022)
Backgrounds: Postoperative urinary retention (POUR) is one of the most common complications after hemorrhoidectomy. The best treatment for POUR is prevention and should be involved in the whole perioperative period. Moxibustion has been used to treat urinary retention for thousands of years, and clinical studies also proved its effects. We try to carry out a randomized, controlled, prospective study to observe whether prophylactic moxibustion could effectively reduce the incidence of POUR of hemorrhoidectomy in 24 hours. Methods: This study is a single-center, evaluator-blinded, randomized, and controlled trial. Participants meet the inclusion and exclusion criteria in this RCT will be randomly assigned to either the treatment group (moxibustion) or the control group (Tamsulosin hydrochloride) by a 1:1 ratio according to a computer-generated randomization list. Both moxibustion and tamsulosin will be used 1 h, 10 h, and 24 h after operation, respectively. The outcomes of occurrence of POUR, time to first urination, catheterization rate, urinary tract infection, length of hospitalization, and adverse effects will be recorded. Discussion: The findings of the study will help to explore the preventive efficacy of prophylactic moxibustion against POUR of hemorrhoidectomy in 24 hours.